Expression of p53 Protein in Different Grades of Gastric Carcinoma - Karim, Rezwana; Afroz, Sadia; Karim, Syeda Noorjahan; Nusrat, Faiza; Sermin, Nafisa; Sen, Sampurna; Shabnam, Ummey Salma; Islam, Tasmia (Mediscope, 2024)
Background: Mutation in the TP53 suppressor gene and accumulation of p53 protein are the common genetic events in gastric carcinomas. This mutation has been associated with abnormalities in cell cycle regulation, DNA repair and synthesis, apoptosis, and suggested to be implicated in the prognosis of gastric carcinoma. Objectives: To assess the immunohistochemical expression of p53 protein in gastric carcinoma and to study the association of p53 protein expression with different histopathological grade of gastric carcinoma. Methods: In this cross-sectional observational study, 60 paraffin blocks of gastric adenocarcinoma were re-evaluated and histopathological grading were assessed. The p53 expression in the tumour cell nucleus of the submitted blocks were assessed by standard immunoperoxidase method. Appropriate positive control was run for each batch of slides. Results: Out of 60 cases, most of them 35 cases were poorly differentiated carcinoma, of which 28(80%) showed high expression and 7(20%) showed low expression of p53 protein. Twenty cases were moderately differentiated carcinoma, of which 12(60%) showed high expression and 8(40%) low expression. Only 5 were well differentiated carcinoma and all of which showed low expression of p53 protein. So, it was seen that with advancing grade of tumor, frequency of high expression of p53 protein was high and yielded statistically significant result (p value = 0.001). Conclusion: There was a significant association between immunohistochemical expression of p53 protein and histopathological grading of gastric adenocarcinoma. These results indicate that immunohistochemical expression of p53 protein is an important prognostic factor of gastric adenocarcinoma, allowing the selection of a group of patients with an extensive therapeutic indication. Mediscope 2024;11(2): 48-51